Boundary and defect CFT: open problems and applications. (20th October 2020) - Andrei, N; Bissi, A; Buican, M; Cardy, J; Dorey, P; Drukker, N; Erdmenger, J; Friedan, D; Fursaev, D; Konechny, A; Kristjansen, C; Makabe, I; et al.
Abstract: A review of Boundary and defect conformal field theory: open problems and applications, following a workshop held at Chicheley Hall, Buckinghamshire, UK, 7–8 Sept. 2017. We attempt to provide a broad, bird's-eye view of the latest progress in boundary and defect conformal field theory in various sub-fields of theoretical physics, including the renormalization group, integrability, conformal bootstrap, topological field theory, supersymmetry, holographic duality, and more. We also discuss open questions and promising research directions in each of these sub-fields, and combinations thereof.